Analysis of pharmaceuticals in indirect potable reuse systems using solid-phase extraction and liquid chromatography-tandem mass spectrometry - Busetti, Francesco; Linge, Kathryn; Heitz, Anna (Elsevier, 2009)
A solid-phase extraction (SPE) LC/MS/MS method for 18 commercial drugs in secondary wastewaterand product water from water recycling plants using microfiltration (MF) and reverse osmosis (RO)has been developed, optimised and validated. The method incorporates a range of multi-class pharmaceuticals including lipid lowering agents, analgesics, antipyretics, non-steroidal anti-inflammatory drugs, antidepressants, anticoagulants, tranquilizers, cytostatic agents, and antiepileptics. Method limits of quantitation (MLQs) in secondary wastewater ranged from 15 to 250 ng/L, while MLQs in post-RO water ranged from1 to 25 ng/L. Results fromanalysis of secondary waste water from Western Australia are presented, and represent the largest survey of non-antibiotic pharmaceuticals within Australia to date. Analysis of post-RO water from two MF/RO water recycling facilities also demonstrate that MF/RO treatment removes most pharmaceuticals to below the analytical limits of detection, and more importantly, up to seven orders of magnitude below health-based guideline values.